An Analysis Of The Impact Of The Medical Device Market And Its Substantial Growth On The Chinese Economy: A Study From The Healthcare Industry Perspective - Zhen Fang, Chu; Aidah Jumuddin, Farra (Cuestiones de Fisioterapia, 2023)
The medical equipment market has a significant impact on china's economic growth via the healthcare sector, and this study explores the importance of the healthcare path of custody in supporting the economy. Traditional distribution strategies place an emphasis on disposable medical items with only one use, endangering both public and environmental health. Environmentally conscious enterprises face several difficulties including concerns around consumer behaviour, regulations and rules, and dealer procedures. The medical device trade in china has seen significant expansion, driven by technological progress, changes to legislation, and increasing healthcare needs. As a result, it is now the second biggest market in the world, after only economic openness. Outside spending, fresh job possibilities, and technological advancement—especially in artificial intelligence-powered medical technologies—have all resulted from this growth, which contributed to improved service delivery while decreasing costs. A statistically significant correlation between the impact of the medical device sector and china's economic growth was confirmed by quantitative research that employed spss and factor analysis to analyse data. Medical device advancements and trade policies impact gdp, technical progress, and health. China gained global notoriety during the pandemic because of its strong supply chains and international cooperation. Even with laws and market rivalry, uniformity and sustainability help this firm. For china to experience economic growth, innovation in healthcare, and long-term prosperity, medical gadgets are of the utmost importance. To bolstering china's financial situation, the government and investors should foster innovation, simplify regulations, and broaden the scope of international engagement.